Prognostic relevance of induced and spontaneous apoptosis of disseminated tumor cells in primary breast cancer patients - Krawczyk, Natalia; Hartkopf, Andreas; Banys, Malgorzata; Meier-Stiegen, Franziska; Staebler, Annette; Wallwiener, Markus; Röhm, Carmen; Hoffmann, Juergen; Hahn, Markus; Fehm, Tanja (BMC cancer, 2014)
An imbalance between cell proliferation and programmed cell death can result in tumor growth. Although most systemic cytotoxic agents induce apoptosis in tumor cells, a high apoptotic rate in primary breast cancer correlates with poor prognosis. The aim of this study was to investigate the incidence and the prognostic significance of apoptotic disseminated tumor cells (DTC) in the bone marrow (BM) of breast cancer patients who either underwent primary surgery or primary systemic chemotherapy (PST).